The Construction of The President and Vice President Positions Under The 1945 Indonesian Constitution - Fuqoha (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
The filling of the positions of President and Vice President is one of the important elements in the administration of the state. In the constitution, it is explained that the holder of governmental power is the President, assisted by a Vice President. Based on the constitution, Indonesia has regulated the mechanism for filling the positions of President and Vice President. The principles of the Indonesian state constitution or the basic law of the Republic of Indonesia contain the principles of democracy. The filling of the positions of President and Vice President underwent changes after the Indonesian Constitutional Amendment, from indirect elections to direct elections. This needs to be a point of attention regarding the meaning of the presidential and vice-presidential election system according to the Constitution. The research method uses a normative juridical approach with a descriptive-analytical type of research. Research results, first, the system of filling the positions of President and Vice President before the Amendment was chosen by the People's Consultative Assembly (MPR), whereas after the Amendment, they were directly elected by the people. Second, the construction of the appointment of the President and Vice President needs to be carried out by philosophically examining the values and spirit of the 1945 Constitution within the framework of representative elections